IMPLEMENTASI PROGRAM PELAYANAN PENEMPATAN TENAGA KERJA ANTAR KERJA ANTAR DAERAH DI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SINTANG - Adinata Teguh. YP E.42009030 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This study aims to determine how the process of program implementation the Agreement on Social Service Manpower Sintang and obstacles that occur during the process of program implementation AKAD.This study uses a qualitative descriptive approach. Data collection techniques are interviews, and documentation. Location of the study at the Dinas Sosial Tenaga Kerja dan Transmigrasi  Sintang Regency. The research subject is Dinsosnakertrans field labor, labor contract and non contract, as well as the company. The conclusion of this study is not optimal implementation of the contract program in search of labor from outside the region and this is because labor is channeled through the contract program can not all be met, there is still a lack of human resources (personnel) that handles this program, in addition to the barrier-barriers that occur in the field resulted in delays in the conduct of the program, except that the procedures are complicated and convoluted to make the company reluctant to search workforce through this program. Keywords: Implementation, program contract, labor, corporate parties.